The dichotomy between urban revitalization and property abandonment: reflections from a sustainability perspective - Moura , Mariana Pereira; Torres , Daniel Henrique da Silva; Barbosa, Ricardo Victor Rodrigues (Technical and Scientific Journal Green Cities, 2024)
This paper aims to discuss the problem of abandoned buildings from the perspective of sustainability. The theoretical article investigates the current situation of these buildings in the city, presenting the environmental, social, economic and cultural aspects. The analysis of the characteristics of the unsustainable urban environment helps to understand how the reuse of empty buildings and lots could promote urban sustainability. At the same time, urban revitalization processes expose a dichotomy, as they cause other problems relating to sustainable practice. The methodology used was based on the evaluation of three urban revitalization projects in former abandoned areas: Lx Factory, Wynwood and Porto Maravilha. The aim of the case studies is to explore the different contexts and scales of the projects, as well as to find congruent aspects through the application of the concept of sustainability and its relationship to both the problems seen with abandonment and the interventions that seek to undermine its effects.